Strategies for Developing Saba Village as a Community-Based Tourism Village in Gianyar Regency - Utama, I Made Agus Purusha; Negarayana , Ida Bagus Putra; Sukariyanto, I Gede Made (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research identifies the development of community-based tourism in Saba Village, Gianyar Regency, with a focus on the economic, social, cultural, environmental, and political dimensions. A qualitative method was employed, involving in-depth interviews and analysis using the IFE, EFE, and Grand Strategy matrices. The results indicate high community participation in tourism activities, with local culture remaining intact without significant acculturation. Environmental management is well-implemented, although the concept of carrying capacity is not fully applied. Community participation in decision-making is quite strong, although collaboration with the private sector is still limited. Based on the grand strategy analysis, Saba Village adopts a Strength-Opportunity (SO) strategy to develop tourism based on local culture, build external partnerships, and optimize technology and community involvement, thus supporting the village's vision of becoming a peaceful, cultural, and prosperous tourist destination.